Determinant of healthcare-seeking behavior for follow-up of toddler pneumonia in Kulon Progo District, 2023 - Sulastri, Yayu; Oktaria, Vicka; Arisanti, Risalia Reni; Sugiarto (BKM Public Health and Community Medicine, 2024)
Purpose: Follow-up visits are crucial to the management of toddler pneumonia. The purpose of this study is to determine the healthcare-seeking behavior (HSB) follow-up visit for toddler pneumonia in the Kulon Progo District. Method: This was an observational study with a cross-sectional study design and a sample size of 185 mothers or caregivers of toddler pneumonia in Kulon Progo District. Data were obtained through interviews using questionnaires. Univariate, bivariate, and multivariate analysis using logistic regression tests. Results: A total of 185 mothers or caregivers were successfully interviewed with a response rate of 96.9%. The percentage of follow-up visits for toddler pneumonia was 65.9%. The multivariate analysis showed that support from healthcare providers (aOR = 7.36 95% CI: 2.38-22.73) and degree of severity (aOR = 3.56, 95% CI: 1.42-8.93) were significantly associated with HSB follow-up visit in toddlers with pneumonia, which was adjusted to family support, caregivers’ knowledge, access to health facilities, number of children, occupation, education of caregivers and toddler sex. Conclusion: Good support from healthcare providers may improve HSB follow-up visits for toddler pneumonia compared to those with less support, with a 7.36 times higher rate. Recommendations for healthcare providers to provide appropriate care, especially those with limited knowledge, in order of increasing caregivers’ knowledge about the necessity of follow-up visits.